Neuropsychology and Transformational Leadership: Integrative Strategies for Managing Students’ Attention, Memory, and Emotions - Ahmad Suyanto Ahmad; Siti Fatimah; Mochamad Nursalim; Diana Rahmasari (Islamic Education Management Study Program, Faculty of Tarbiyah, Sunan Drajat Islamic Boarding School Institute, Lamongan, East Java, Indonesia., 2026)
Elementary education faces complex challenges in managing students' learning processes involving cognitive (attention and memory) and affective (emotion) aspects. Transformational leadership of school principals plays a strategic role in creating a learning ecosystem that supports the optimization of students' neurocognitive functions. This research library aims to analyze the integration between neuropsychological principles (attention, memory, and emotion) and transformational leadership practices in elementary education, as well as formulating effective management strategies. The method used is a systematic literature review analyzing 18 sources covering Atkinson-Shiffrin's information processing theory, educational neuropsychology, transformational leadership, and research on emotion and learning. The results show that (1) students' attention can be managed through leadership strategies that create distraction-free environments and optimal stimulation; (2) working and long-term memory can be optimized through structured repetition, meaningful learning, and information elaboration; (3) positive emotions (happiness) increase memory encoding efficiency, while negative emotions (anxiety, sadness) disrupt retention and recall processes. Transformational leadership contributes through exemplary behavior, inspirational motivation, intellectual stimulation, and individual consideration. This study recommends an integrative leadership model based on neuropsychology to improve learning quality in elementary education.